“Emergent Countries Play, Too!”: The Zeebo Console as a (Partial) Decolonial Project - Paula, Bruno de (Revista Contracampo, 2021)
The present paper discusses questions related to the histories of videogames, more specifically in how we approach videogames in Global South. By using Zeebo, a Brazilian console produced in the late 2000s as an epistemic tool, I discuss the limitations of universalist, mainstream-centric epistemological models for exploring videogames as cultural phenomena. By investigating Zeebo’s discourses about piracy and players in the Global South, I argue that this platform can be seen as a partial decolonial project, destabilising conventional historical narratives about South-North relationships in videogames, but refraining from challenging a mainstream, Global North oriented epistemology. This exploratory work, therefore, elaborates on how a decolonial project of history of videogames, one that is more epistemically just to Global South, could be sought.
Number: 2
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 4-Europe (lieu de production du savoir); 5-Créatrice; _Nettoyé

Interview with Mira Wardhaningsih from StoryTale Studios on the Indonesian Horror Game Pamali - Trattner, Kathrin; Wardhaningsih, Mira (Gamevironments, 2019)
An interview by Kathrin Trattner with Mira Wardhaningsih, Cultural Content Director from StoryTale Studios about the game Pamali
Accepted: 2020-03-25T23:30:30Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé

Crash Override: How Gamergate (Nearly) Destroyed My Life, and How We Can Win the Fight Against Online Hate - Quinn, Zoë (PublicAffairs, 2017)
You've heard the stories about the dark side of the internet – hackers, #gamergate, anonymous mobs attacking an unlucky victim, and revenge porn – but they remain just that: stories. Surely these things would never happen to you. Zoe Quinn used to feel the same way. She is a video game developer whose ex-boyfriend published a crazed blog post cobbled together from private information, half-truths, and outright fictions, along with a rallying cry to the online hordes to go after her. They answered in the form of a so-called movement known as #gamergate–they hacked her accounts; stole nude photos of her; harassed her family, friends, and colleagues; and threatened to rape and murder her. But instead of shrinking into silence as the online mobs wanted her to, she raised her voice and spoke out against this vicious online culture and for making the internet a safer place for everyone. In the years since #gamergate, Quinn has helped thousands of people with her advocacy and online-abuse crisis resource Crash Override Network. From locking down victims' personal accounts to working with tech companies and lawmakers to inform policy, she has firsthand knowledge about every angle of online abuse, what powerful institutions are (and aren't) doing about it, and how we can protect our digital spaces and selves.Crash Override offers an up-close look inside the controversy, threats, and social and cultural battles that started in the far corners of the internet and have since permeated our online lives. Through her story – as target and as activist – Quinn provides a human look at the ways the internet impacts our lives and culture, along with practical advice for keeping yourself and others safe online.
Google-Books-ID: gpvUDQAAQBAJ
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Étude des industries culturelles; 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créatrice; _Nettoyé

Queer Game Studies - Ruberg, Bonnie; Shaw, Adrienne (University of Minnesota Press, 2017)
The in-depth, diverse, and accessible essays in Queer Game Studies use queerness to challenge the ideas that have dominated gaming discussions. This volume reveals the capacious albeit underappreciated communities that are making, playing, and studying queer games, demonstrating the centrality of LGBTQ issues to the gamer world and establishing an alternative lens for examining this increasingly important culture.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créatrice; _Nettoyé